Pembelajaran Membaca Lanjutan di Sekolah Dasar - Hamra Amelia; Hamzah, Rahma Ashari; Fat Aristia (Celebes Journal of Elementary Education, 2025)
This study aims to comprehensively examine advanced reading instruction in elementary schools as a crucial stage in developing students' literacy skills. It covers the definitions, objectives, and types of advanced reading aligned with the characteristics of elementary school students, and reviews strategies such as SQ3R, paired reading, graphic organizers, and literature circles, which have been proven effective in enhancing reading comprehension. The method used is a literature review through the analysis of relevant scholarly sources. The findings show that these strategies support improved comprehension, collaboration, critical thinking, and active student engagement. This study also discusses implementation challenges and offers directions for creative innovation in the context of advanced reading instruction. The novelty of this study lies in its integrative analysis of advanced reading strategies tailored to the diverse characteristics of elementary students, along with the incorporation of interactive educational digital media—an approach still relatively rarely explored in basic literacy literature.